2023
DOI: 10.1155/2023/8206298
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Total Bilirubin Level and Patients with Primary Open-Angle Glaucoma in China: A Cross-Sectional, Case-Control Study

Abstract: Objective. To investigate the relationship between peripheral blood total bilirubin (TBIL) levels and the risk of primary open-angle glaucoma (POAG). Methods. This study was a cross-sectional, case-control study design. Between April 2021 and January 2022, 198 POAG patients and 205 healthy subjects were recruited from the EENT Hospital of Fudan University. Their clinical information (intraocular pressure, central corneal thickness, vertical cup-disk ratios (VCDR), and axial length) and demographic data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Experimental studies have shown that total bilirubin can effectively scavenge ROS and inhibit the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, ultimately reducing oxidative stress [ 60 ]. Shao et al demonstrated that high TBIL levels are a risk factor for POAG in men, but not in women [ 61 ]. A retrospective case-control study indicated that glaucoma patients had lower serum albumin and bilirubin levels than healthy controls [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that total bilirubin can effectively scavenge ROS and inhibit the activity of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, ultimately reducing oxidative stress [ 60 ]. Shao et al demonstrated that high TBIL levels are a risk factor for POAG in men, but not in women [ 61 ]. A retrospective case-control study indicated that glaucoma patients had lower serum albumin and bilirubin levels than healthy controls [ 62 ].…”
Section: Discussionmentioning
confidence: 99%